OPTIMIZING DONOR ENGAGEMENT TO INCREASE GENEROSITY: STRATEGIESWHICH FOCUSES ON PROFILE DIVERSIFICATIONAND INDIVIDUAL NEEDS INCHARITABLE GIVING ENVIRONMENTTHE OPEN - Aripin, Zaenal; Ichwanudin, Wawan; Faisal, Ijang (Organisasi Kreatif Indonesia Emas, 2024)
In the era of open charitable giving, optimizing donor engagement and increasing generosity requires a thoughtful and targeted approach. One key strategy is diversification of donor profiles and a deep understanding of individual needs. This article explores the role of technology in supporting these strategies and its impact on donor engagement and the overall effectiveness of nonprofit organizations. By collecting and analyzing donor data using a CRM system, organizations can better understand donor profiles, identify trends, and design more tailored approaches. Predictive analytics also allows organizations to predict future donor behavior, so they can adjust their fundraising strategies more effectively. Additionally, technology enables personalized communications with donors through email marketing, social media, and chatbots, strengthening bonds with donors and increasing their engagement. In the context of open charitable giving, transparency and accountability in fund management are important factors in influencing donor engagement. Organizations need to continue to increase transparency in fund management and utilize technology wisely to respond effectively to donor needs.